Grado de conocimiento sobre la paracloroanilina en los odontólogos pertenecientes a la Dirección Distrital de Salud N° 11D01 de la ciudad de Loja. 2018 - Carrión Gordillo, Sonia Elizabeth (2019)
The purpose of this study was to evaluate the degree of knowledge about Paracloroaniline in Dentists of the District Health N° 11D01 of Loja City. The sample consisted of 19 professionals who serve in each of the District's Health. By means of a survey applied to professionals, it was possible to determine what type of substances are used for the irrigation of root canals in endodontic treatment. The data collected after the survey were analyzed, and and concluded that 74% (n=14) of the professionals surveyed use Sodium Hypochlorite, 21% (n=4) use Chlorhexidine and 5% (n=1) use EDTA; That 58% (n=11) do not use simultaneously Sodium Hypochlorite and Chlorhexidine; However, 32% (n=6) regularly use both substances combined in the same treatment and 11% (n=2) mentioned that they always use both substances in the same endodontic procedure; Finally, that 58% (n=11) of Dentists have no knowledge of Paracloroanilina and 42% (n=8) mentioned having knowledge about this substance. Keywords: Precipitate, Paracloroaniline, Sodium Hypochlorite, Chlorhexidine.